Proses Pengembangan Social Enterprise Agriculture: Studi Biografi Pada Agradaya - Karlin Maulinda (Jurnal Studi Pemuda, 2018)
Social entrepreneurship in Indonesia is growing rapidly today. Social entrepreneurship is an alternative solution in the social solution of society with entrepreneurship. One of the social entrepreneurship organizations in Yogyakarta is Agradaya which is engaged in agriculture. Agradaya is optimizing agricultural production. This study identifies the process of social entrepreneurship using the concepts of Perrini and Vurro. The method used in this study is a qualitative biography study approach that expresses the experiences of attracting actors in the process of developing social entrepreneurship. Data collection techniques are carried out by observation, interviews, and document search. The selection of informants is purposive which directly leads to goals. In this study the focus was on the two founders of Agradaya, Andhika and Asri. Supporting informants consist of farmers who are members of a women's farmer group (KWT) Menoreh guided by Agradaya. Data analysis is done by categorizing data, describing, and data presented in the form of narrative stories along with graphics, schemes, and drawings, then draw conclusions. The results obtained in this study are that Agradaya starts the practice of social entrepreneurship directly as a social enterprise. The results of the research show that in the process of development Agradaya approaches farmers and collaborates. There is encouragement from each of the founders to solve social problems in agriculture by conducting natural agricultural education, land management, educating the use of solar dryer technology in the process of adding value to the sale price, as well as open access to information and markets for farmers.